De Tito à Alexandre : vers la construction d’un paysage urbain postsocialiste à Skopje (République de Macédoine) ? - Hervé Amiot (Belgeo)
This paper questions the symbolic transformations of urban space in Skopje, the capital of Republic of Macedonia, since 2010. ’Skopje 2014’ project is part of a larger policy of rewriting history around Antiquity. It aims at erasing Yugoslav material heritage from urban space and reshaping the city with a new iconography. This paper, based on a fieldwork combining landscape analysis and interviews, identifies the iconography spread by the project as well as the form taken by the transformations. The strategies of reshaping old building and constructing new monuments at precise locations have created new visual configuration that modify the city center landscape in depth. Base on the case of Skopje, I draw a landscape analysis grid that can be used to read policies of nation building in other urban contexts.